Predictors of early mortality among patients with acute‐on‐chronic liver failure. Issue 6 (19th May 2021) - Valantine, Bershic; Sundaray, Nabakishore; Mishra, Debakanta; Sahu, Samir; Narayan, Jimmy; Panda, Baikuntha N; Singh, Ayaskanta
Abstract: Background and Aim: Acute‐on‐chronic liver failure (ACLF) is a transpiring entity, which possesses high short‐term/early mortality (28 days). Several mortality predictors have been studied, but none were proved reliable. Serum ferritin, an acute phase reactant and marker of hepatic necro‐inflammation, is found to predict mortality in multiple liver diseases. We aimed to evaluate the role of serum ferritin and other clinical features, biochemical parameters and conventional scoring systems in predicting early mortality among ACLF. Methods: A prospective cohort study was done from October 2017 to March 2019 at a tertiary care (non‐transplant) center in eastern India. A total of consecutive 50 ACLF patients diagnosed, based on Asia Pacific Association for the Study of liver disease definition, were investigated for ferritin and other laboratory parameters on day‐0, day‐7, and followed up for 28 days. Results: Although the majority did not have organ failure (ACLF grade 0) according to European Association for Study of Liver‐chronic liver failure sequential organ failure assessment criteria, early mortality was high (56%). On undergoing univariate analysis, multiple variables (ascites, HE, creatinine, total leucocyte count (TLC), bilirubin, albumin) predicted mortality. However, on multivariate analysis, only total bilirubin independently predicted. None of the scores on day‐0 were predictive, while model for end‐stage liver disease [area under the receiver operating characteristics (AUROC)‐0.703, 95% confidence interval [CI]: 0.535–0.859] and Child–Turcotte–Pugh (AUROC‐0.697, 95% CI: 0.550–0.855) on day‐7 did. Conclusion: ACLF is a dynamic process; day‐7 assessment with above predictors, to be considered a milestone for prognostication and opting treatment modalities. Serum ferritin does not predict early mortality in ACLF. Abstract : A prospective cohort was done in a tertiary non‐transplant center in eastern India, in order to evaluate the predictors of early mortality in acute‐on‐chronic liver failure. The well‐known inflammatory marker, serum ferritin was hypothesized as a novel mortality predictor and was also evaluated. The study revealed serum bilirubin, Child–Turcotte–Pugh score, and model for end‐stage liver disease, on day‐7 following admission, as the independent predictor of mortality; serum ferritin failed to predict.